1997
DOI: 10.1001/archinte.157.16.1885
|View full text |Cite
|
Sign up to set email alerts
|

Spook house sporotrichosis. A point-source outbreak of sporotrichosis associated with hay bale props in a Halloween haunted-house

Abstract: While isolated cases of sporotrichosis typically occur following contact with contaminated plant materials, outbreaks are distinctly unusual. A temporal increase in the incidence of sporotrichosis in a dermatology practice at a military installation in southwestern Oklahoma prompted an investigation. Patients with sporotrichosis presenting to a single dermatologist in the winter of 1992-1993 were interviewed, epidemiological data were collected, and fungal cultures were obtained from incriminated hay fields. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
2
19
0
3
Order By: Relevance
“…[2][3][4][5]26 For this reason, sporotrichosis is considered to be acquired during outdoor leisure or occupational activities (eg, farming and gardening) that promote frequent and traumatic contact with plant material or soil. [27][28][29] In agreement with these observations, our study found that 74.3% of patients presented an occupational hazard, although no evident hazard could be established for the remaining 25.6% of patients.…”
Section: Discussionsupporting
confidence: 87%
“…[2][3][4][5]26 For this reason, sporotrichosis is considered to be acquired during outdoor leisure or occupational activities (eg, farming and gardening) that promote frequent and traumatic contact with plant material or soil. [27][28][29] In agreement with these observations, our study found that 74.3% of patients presented an occupational hazard, although no evident hazard could be established for the remaining 25.6% of patients.…”
Section: Discussionsupporting
confidence: 87%
“…In the United States, LS in children has usually been reported in limited epidemics and small clusters [22][23][24][25]. With the exception of a previous report from this area [11], children are usually found to constitute only a minority of the patients with LS [12][13][14][15][16][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Another outbreak was epidemiologically associated with bales of hay from a Halloween haunted house (there was no residual hay to culture, and cultures from the implicated fields 5 months after exposure were negative for S. schenckii). 67 Such bales are often purchased for yard decorations. The author is personally acquainted with a poorly controlled diabetic who died of disseminated sporotrichosis acquired via a thorn puncture from her home garden in Illinois.…”
Section: 57mentioning
confidence: 99%